(untitled) (Al-Academy, 2016)
The problem with the research essential questionably is: (What are the variations phenotypic designs decorative Alangat) The research aims detection of phenotypic variables and Acgalah in Wares structure decorative employee in the decorative designs in the external and internal interfaces to the tombs of the Iraqi holy shrines and the walls of b (upper threshold _ Najaf) Alattabatin Husseinia and Abbasid in the holy city of Karbala) current position (1435 AH / 2014 AD). And ensure that the theoretical framework topics following: diversity in the structure motifs and vegetable processors color as well as landmarks decking decorative decorative gift items and adopted a researcher at the procedures purely on the descriptive analytical approach in order to reach to achieve his findings samples were selected is my intention as numbered sample (8). As a result of the analysis process set of results, including: through the analysis found that there are variations in the structure of decorative Wares (in terms of exterior appeared) 1 . Decorative pots with lobed nozzle-free flowers neck Bhaoh knots Association to form three-element Casey Daybreak caused by a pair of knobs, and her body tapering from the top and plenty of down based on containing the base of the hull of the board inspired by the element Casey tri Daybreak hollow bottom.2 .Pots, decorative with nozzle straight devoid of flowers overlapped her neck with a bottom round and has a pair of handles are linked to the body knot inspired by the tinea Leaf shape Association, and the body expanding the top and Almstdq from the bottom, while the base are Bhaoh misdemeanor, and another with a mouth of straight laden with floral her body similar to the form bulbar inverted partial top and bottom filled with excerpts crescent repeated on a regular basis and the base of the tapered top and widening towards the bottom. .3 . Decorative vessels laden with mouth of floral and plant leaves that are superimposed show her neck is linked to the body color and form a relatively slim body and widening of the top and bottom of Almstdq based on a concave base is like the pot ..Amamn where decorative works of the vessels was adopted on:1 .decorative works within diverse parts of the immediate establishment of a single species (Casey Zuhri) and the creation of two types (Pink Cups) and (Casey Gsna, and gift items of works (Casey) within a double portion and set up within the other parts.2 .held somewhat decorative gift items unilaterally with floral character and surrounded by views of the natural Created decorative vase with floral vocabulary.3 .decorative gift items with the establishment (Casey) Solid fully chromatically, and served other gift items creation (Casey) Unlike our surroundings subsistence .